Public innovation in Brazil: An overview of its types,results and drivers - Pedro Cavalcante; Marizaura Cam\~oes (Institute for Applied Economic Research (ipea), 2017)
Practitioners and scholars of public administration currently seem to have overcome comprehensive reform strategies and are focusing their attention on minor changes in public administration that generate short-term outcomes with lower transactional costs. In that sense, many have argued that innovation can contribute to improve the public service quality and efficiency as well as to enhance government capacity in solving problems. In Brazil, specifically, there is a certain degree of consensus about the increase of management innovation practices over the last two decades. However, as in other countries, the lack of evidence-based knowledge regarding different dimensions of innovation prevails. One important dimension that must be deeply investigated is the innovation's determinants. In other words, which factors influence the public sector innovation initiatives? The paper aims to answer this relevant question. This paper's original data comes from the Federal Management Innovation Award (FMIA), the most important innovation prize in Brazil, conducted by the National School of Public Administration (Enap), to recognize innovative practices that have improved government capacity and service delivery. Every year, twenty initiatives are nominated to the final and ten are awarded as the most innovative management practices. Using quantitative dataset, built from content analyzes of these initiatives' reports from 2007 to 2015, we examine their influential factors. The research results confirm the hypothesis that innovation is not an isolated construct, in other words, its determinants tend to be also influenced by the relationships with the types and phases of the innovation.
Keywords: H1; H11; 330; Innovation; public administration; management; federal government